Problematika Pembelajaran Pendidikan Agama Islam dan Upaya Solusi Guru Agama dalam Pembinaannya di Sekolah - Muslimin, Muslimin (Tarbawiyah Jurnal Ilmiah Pendidikan, 2017)
This article describes the problematic learning of Islamic religious education and the efforts of religious teacher solutions in coaching in schools. Today, teachers-especially Islamic religious teachers are faced with a very complicated and complicated problem, so that teachers are demanded for professionals. In addition to experts in the field of teaching and educating, teachers also have the authority and autonomy as well as full responsibility to educate learners. Therefore, professional teachers prepare themselves well before they teach. Among the problems experienced by religious teachers in the learning process of PAI include several things, namely; problematic of formulation of learning objectives, learning materials and their mastery, selection of appropriate methods, media usage, evaluation implementation. Meanwhile, solutions to solve this problem, among others; attending subject matter teachers; make use of available books or resources; often religious teachers hold discussions with experts; follow special education.